Imprisonment worldwide : the current situation and an alternative future - Coyle, Andrew (Ph. D. in criminology); Fair, Helen; Jacobson, Jessica, 1966-; Walmsley, Roy (Policy Press shorts. Insights., 2016)
How many people are imprisoned across the globe? What factors can help explain variations in the use of imprisonment in different countries? What ethical considerations should apply to the way imprisonment is used? Providing a comprehensive account of prison populations worldwide, this new work links prison statistics from the last 15 years with considerations of how prisons and prison populations are managed. With commentary from its well-known, respected authors on what is meant by an ethical approach to the use of imprisonment, and how this can be sustained in ever more challenging social, economic and political environments, this book is a major contribution to the knowledge of those currently debating prisons and the use of imprisonment, whether from academic, policy, practitioner, activist or lay perspectives. Its accessible, informative infographics also make it an engaging read and a valuable teaching resource for undergraduate and postgraduate courses in criminology, law, political science, and public policy.